2016
DOI: 10.1093/jhered/esv098
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Paternity in the Norway Rat,Rattus norvegicus, from Urban Slums in Salvador, Brazil

Abstract: The Norway rat, Rattus norvegicus, is one of the most important pest species globally and the main reservoir of leptospires causing human leptospirosis in the urban slums of tropical regions. Rodent control is a frequent strategy in those settings to prevent the disease but rapid growth from residual populations and immigration limit the long-term effectiveness of interventions. To characterize the breeding ecology of R. norvegicus and provide needed information for the level of genetic mixing, which can help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…Rats have been observed moving over 150 m in a day (Glass et al., ; Recht, ), but their home range is often as small as 30–40 m in urban settings (Davis et al., ). Additionally, paternity tests (Costa et al., ; Glass et al., ) and radio tracking (Taylor & Quy, ) indicate that male rats regularly expand their range of movement to find mates, often moving hundreds of metres. Our study describes distances separating related pairs of individuals that may be due to dispersal or regular home range movement by one or both rats in each dyad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats have been observed moving over 150 m in a day (Glass et al., ; Recht, ), but their home range is often as small as 30–40 m in urban settings (Davis et al., ). Additionally, paternity tests (Costa et al., ; Glass et al., ) and radio tracking (Taylor & Quy, ) indicate that male rats regularly expand their range of movement to find mates, often moving hundreds of metres. Our study describes distances separating related pairs of individuals that may be due to dispersal or regular home range movement by one or both rats in each dyad.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that only a small percentage of urban rats move between study sites, with greater movement identified by genetic methods (6.5%, Gardner‐Santana et al., ; 6.8%, Kajdacsi et al., ) than capture–mark–recapture studies for rats caught above ground (0.003% between city blocks, Davis, ) or below ground (0.0% between sewer systems, Heiberg et al., ). Movements by adult males presumably maintain gene flow between nearby colonies (Costa et al., ; Glass, Klein, Norris, & Gardner, ), but results on sex‐biased dispersal have been mixed (Gardner‐Santana et al., ; Heiberg et al., ; Kajdacsi et al., ). However, urban rats are capable of moving several kilometres during relatively rare long‐distance dispersal events (Creel, ), indicating the possibility of gene flow across entire cities.…”
Section: Introductionmentioning
confidence: 99%
“…Norway rats exhibit colonial social systems, where individuals within a colony are more related to each other than at random among the population (Calhoun, 1963;Costa et al, 2016). However, drastic reductions in population size may disrupt this social structure, leading to shifts in relatedness if some colonies are hit harder than others, or if the residual individuals remaining after the campaign come from a subset of colonies and inbreeding increases (Calhoun, 1963).…”
Section: Relatednessmentioning
confidence: 99%
“…However, the sharp break in genetic similarity between Valley 2 and Valley 4 indicates the potential for such adaptive divergence to either arise or explain the observed genetic break. Outbreeding avoidance may also contribute to this divergence, where rats are more likely to breed with more closely related individuals coming from within the local population, rather than immigrants from other areas of Pau da Lima or Salvador (Costa et al., ). There are an increasing number of examples of evolutionary divergence at microgeographic scales, including in response to complex urban environments and their natural selection regimes (Richardson et al., ; Saccheri, Rousset, Watts, Brakefield, & Cook, ; Selander & Kaufman, ).…”
Section: Discussionmentioning
confidence: 99%